Determining responsiveness and meaningful changes for the Musculoskeletal Health Questionnaire (MSK-HQ) for use across musculoskeletal care pathways. Issue 10 (3rd October 2019) - Price, Andrew James; Ogollah, Reuben; Kang, Sujin; Hay, Elaine; Barker, Karen L; Benedetto, Elena; Smith, Stephanie; Smith, James; Galloway, James B; Ellis, Benjamin; Rees, Jonathan; Glyn-Jones, Sion; et al.
Abstract : Objectives: We have previously developed and validated the Arthritis Research UK Musculoskeletal Health Questionnaire (MSK-HQ) for use across musculoskeletal care pathways, showing encouraging psychometric test results. The objective of this study was to determine the responsiveness of MSK-HQ following MSK treatments and to determine the minimally important change (MIC). Setting: We collected data in four cohorts from community physiotherapy and secondary-care orthopaedic hip, knee and shoulder clinics. Participants: 592 individuals were recruited; 210 patients treated with physiotherapy for a range of MSK conditions in primary care; 150 patients undergoing hip replacement, 150 patients undergoing knee replacement and 82 undergoing shoulder surgery in secondary care. Outcome measures: Preoperative data were collected including the MSK-HQ, European Quality of Life-5D (EQ-5D) and the OHS, OKS or OSS in each joint-specific group. The same scores, together with anchor questions, were collected postintervention at 3 months for the physiotherapy group and 6 months for all others. Following COnsensus-based Standards for the selection of health status Measurement INstruments (COSMIN) guidelines, responsiveness was assessed using correlation between scores and the MIC was calculated for the entire cohort using receiver operating characteristic curve analysis. Results: The MSK-HQ demonstrated strong correlation (R=0.73) with EQ-5D across the entire cohort and with each of the joint-specific Oxford scores (hip R=0.87, knee R=0.92 and shoulder R=0.77). Moderate correlation was seen between MSK-HQ and EQ-5D across each individual group (R value range 0.60–0.68), apart from the hip group where correlation was strong (R=0.77). The effect size with MSK-HQ was 0.93, in the entire cohort, double that measured with EQ-5D (0.43). In all subgroups, MSK-HQ measured a greater treatment effect compared with EQ-5D. The MIC is 5.5 (95% CI 2.7 to 8.3). Conclusion: Our study demonstrates that the MSK-HQ questionnaire is responsive to change across a range of musculoskeletal conditions, supporting its use as a generic MSK measurement instrument.